2015
DOI: 10.1039/c5tc00237k
|View full text |Cite
|
Sign up to set email alerts
|

Toward a new generation of white phosphors for solid state lighting using glassy yttrium aluminoborates

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
3
22
2
1
Order By: Relevance
“…[1] In ar ecent work, we reported bright white emission in amorphous yttrium aluminum borate (a-YAB) powders,free of lanthanides or other metal-active ions. [9,10] These powders obtained by am odified Pechini method have ac omposition close to YA l 3 (BO 3 ) 4 after thermal treatments.T he PL iQY is about 90 %u nder NUV excitation at 365 nm with high color rendering indexes (92-94), ideal for white LED devices under NUV excitation. On the other hand, we also showed that the PL efficiencyo fa -YAB powders exhibits ac orrelation with the presence of paramagnetic centers (radicals) evidenced by electron paramagnetic resonance (EPR) spectroscopy.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…[1] In ar ecent work, we reported bright white emission in amorphous yttrium aluminum borate (a-YAB) powders,free of lanthanides or other metal-active ions. [9,10] These powders obtained by am odified Pechini method have ac omposition close to YA l 3 (BO 3 ) 4 after thermal treatments.T he PL iQY is about 90 %u nder NUV excitation at 365 nm with high color rendering indexes (92-94), ideal for white LED devices under NUV excitation. On the other hand, we also showed that the PL efficiencyo fa -YAB powders exhibits ac orrelation with the presence of paramagnetic centers (radicals) evidenced by electron paramagnetic resonance (EPR) spectroscopy.…”
mentioning
confidence: 75%
“…On the other hand, we also showed that the PL efficiencyo fa -YAB powders exhibits ac orrelation with the presence of paramagnetic centers (radicals) evidenced by electron paramagnetic resonance (EPR) spectroscopy. [9] Nevertheless,t he exact nature of the emitting centers in such promising PL materials is not yet accurately identified.…”
mentioning
confidence: 99%
“…However, there is no clear correlation between the Pr content and the intensity of this signal. Although the presence of the half resonance at g = 4.3 implies that a half res- onance signal at g = 2.1 ( m s = ±1) should be observed, it is hard to distinguish the corresponding signal around 3500 G (g = 2.1), due to the strong background signal at around 3000 G. The small signal at g = 2.0, which was previously attributed to the NBO or peroxide radicals hole traps [39], is clearly confirmed only for the un-doped glass (x = 0), and no such clear signal is observed for other compositions (x = 0.5 and 1.0). In view of the relationship between the intensity of TSL glow curves and the Pr concentration, it appears that the origin of TSL, i.e., traps present in the host, are not ESR active species.…”
Section: Resultsmentioning
confidence: 94%
“…Finally, they are easily workable and can be prepared in a variety of forms and geometry including optical fibres. In particular, yttriaaluminoborate (YAB) and, more generally, lanthanide oxide-aluminoborate glasses have been proved to be a suitable matrix for RE incorporation and for the realization of optical materials thanks to their chemical durability, high transparency and mechanical strength [2][3][4][5][6]. Within the compositions available in the glassforming region of the Y 2 O 3 -Al 2 O 3 -B 2 O 3 system [2,7], a relevant role as possible interesting optical materials can be found for composition with molar ratios close to that of YAl 3 (BO 3 ) 4 .…”
Section: Introductionmentioning
confidence: 99%